The optimal cash holdings speed of adjustment and firm value: An empirical study in Indonesia - Heru Kristanto Hendro Cahyono; Mamduh M Hanafi; Bowo Setiyono (Jurnal Keuangan dan Perbankan, 2019)
This study employs two models of the speed of cash holdings adjustment to measure the effect of cash management on firm value, they are the deviation standard cash holding model and partial speed of adjustment model. Using sampling companies from Indonesia during 2001-2017, the study employs some techniques of regression for dynamic panel data with fixed effects, the pooled ordinary least square with fixed effects, and regression moderated analysis. Research findings show that: first, the deviation standard cash holding and partial speed of adjustment affect firm value; second, by using the deviation standard cash holding model,  it shows that managerial ownership, institutional ownership, investment and debt moderate the effect of the deviation standard cash holding on firm value; third, by using the partial speed of adjustment model, it shows that investment moderates the effect of partial speed of adjustment on firm value. The implications of the study are to explain two speed of cash holding adjustment models and their impacts on the increasing trend of firm value.JEL Classification: C33, G31, G34DOI: https://doi.org/10.26905/jkdp.v23i2.2604